Space configuration as an adaptation element of Madurese migrant urban settlements in Malang - Asikin, Damayanti; Antariksa; Wulandari, Lisa Dwi; Rukmi, Wara Indira (Journal of Architecture and Urbanism, 2020)
Humans interacting with their physical and social environments always try to adapt individually or in groups. In the adaptation process, a space dynamic will occur and cause space changes. Adaptation elements include the physical environment, socio-cultural environment, and behavior. Interaction among the adaptation elements will form changes to space configuration. Kotalama is the largest Madurese migrant settlement in Malang and was established in the 1950s. Research on space configuration was conducted to study the adaptation elements in the interaction process of the migrants and their environment. The research used a qualitative, descriptive method and inductive analysis to gain insights on the relationship to dwellings on Madura Island. Data were collected through observations of dwelling space configuration. In addition, in-depth interviews with key informants were held. The results show that the space configuration of dwellings in Kotalama contain elements of adaptation and interaction between the migrants and their environment. These elements relate to Madurese ethnic identity, which are influenced by local topographical factors and limited by the size of the settlement area. First published online 17 January 2020